(untitled) (Journal of Innovation in Academia, 2025)
This study mainly attempts to explore the positions of employees’ job satisfaction and to analyze the impact of job satisfaction on change readiness. To explore the position, cross sectional research under descriptive research design and casual research design have been adopted respectively. Based on the primary data collected from branch managers of Global IME Bank, the researcher explored the impact of job satisfaction on change readiness. The position of managers’ job satisfaction was found to be above to the average in investigated banks. It was also identified significant positive relationship between job satisfaction and change readiness and no significant difference in change readiness in different groups of gender, age, level of education and length of employment.